SERVICE QUALITY AND PRODUCT QUALITY AS AN INFLUENCE ON CUSTOMER LOYALTY AT NATURALIS KOFFIE - Vera Loestefani; Roy Poan; Benyamin Suwito Rahardjo; Akhmad Kusuma Wardhana (President University, 2022)
This study aims to examine the role of service quality such as time efficiency, price, atmosphere, employee attitudes, information technology quality, aesthetics, escapism and product quality as an influence on consumer loyalty at “Naturalis Koffie”. Quantitative methods with primary data were used in this study. Data is collected using online questionnaires find the right respondents, that have visited Naturalis Koffie. The data gather were analyzed using Partial Least Square - Structural Equation Modeling (PLS-SEM) on SmartPLS 3.2.9 application. The results show that customer loyalty is influenced by service quality – consisting of 9 subdimensions: Time efficiency, Fairy Price, Atmosphere, Employee Attitude, Information Technology Service, Coffee Quality, Aesthetics, Escapism, and Satisfaction. The study found that all the nine variables were important interm of key success of the café. The originality of this study was to determine the effect of Service quality and product quality as an influence on consumer loyalty that affect costumer repeat order.